Analisis Kapasitas Terminal Kargo Menurut Peraturan Menteri Perhubungan Nomor Km 29 Tahun 2005 di Bandar Udara El Tari Kupang Nusa Tenggara Timur - Jorina, Carmelita Crisma D Putri; Widagdo, Djoko (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The cargo terminal is one of the main service facilities in the airport which aims to smooth the cargo process, for those who go out and in supported by adequate facilities and warehouses as stipulated in the Minister of Transportation Regulation concerning SNI 03-7047-2004 regarding airport cargo terminals so that flights can run smoothly, safely and safely. This study aims to determine the capacity of the cargo terminal and the application of Standard Operating Procedures (SOP) at the incoming cargo terminal at PT Angkasa Pura I at El Tari Kupang Airport, East Nusa Tenggara. This type of research is mix method. To obtain the results of this study using interview, observation and documentation methods conducted during the research. After obtaining the necessary data, the researcher will process the data into a discussion and make conclusions and suggestions. Based on the results of the research obtained by the researcher that the cargo terminal warehouse at El Tari Kupang airport is inadequate where the amount of incoming cargo production is greater than the capacity of the existing cargo warehouse especially during peak hours from the calculations that have been carried out, the cargo terminal warehouse at El Tari Kupang airport has met the standard guidelines stated in the Minister of Transportation Regulation No KM 29 of 2005. Although it has been found that the cargo terminal has met the applicable standards, the cargo terminal at El Tari Kupang airport still cannot accommodate cargo goods that arrive in large quantities resulting in overload in the incoming cargo warehouse. This can be influenced by several factors, namely high demand, errors in planning and lack of supporting facilities. In handling incoming cargo, the application of Standard Operating Procedures (SOP) at the incoming cargo terminal has been carried out in accordance with the applicable domestic cargo and postal service quality procedures. Keywords: Capacity, Cargo Terminal, Standard Operating Procedure (SOP).